Towards a ‘figured’ and ‘imagined’ world for the Colombian Applied Linguistics Journal - Castañeda-Peña, Harold (Colombian Applied Linguistics Journal, 2014)
Welcome to this new issue of the Colombian Applied Linguistics Journal. This time a new layout is presented addressing the challenges of becoming a digital journal for the appliedlinguist academic community. This effort has been cooperatively constructed by the joined efforts of the CIDC Journal Coordinator at Universidad Distrital Francisco José de Caldas, the Editorial and Scientific Committees, the editor and his editorial assistant and the valuable contributions made by authors and peer reviewers. As expressed by Holland, Skinner, Lachicotte and Cain (1998) in relation to identity and agency, this making of a figured world for our journal has been a heteroglossic exercise where multiple voices are entangled together and where the vantage point of our dialogism rests in a plural collective experience that shapes angles of a revisited identity.